PERBANDINGAN PENYARADAN KAYU DENGAN SISTIM MANUAL DAN EKSAVATOR DI HUTAN RAWA BAGIAN Ill : KAJIAN TEKNIS, EKONOMIS DAN EKOLOGIS - Wesman Endom; Zakaria Basari (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
Modified excavator is one of heavy equipment that might be useful and environmentally friendly to be used for operational logging extraction especially in swampforest. It is therefore besides convenient and powerful, it is also helpful as an effective alternative in anticipating the weakness of manual system which is called